(untitled) (Raparin Journal of Humanities (RJH), 2026)
The research aims to know the relationship and impact of smart leadership represented by its dimensions (emotional intelligence, rational intelligence, spiritual intelligence, personal intelligence) on the dimensions of strategic recovery represented by (speed, apology, compensation, initiative) from the point of view of managers in Korek Telecom Company in the Kurdistan Region of Iraq. The general framework of the research is represented by the research problem, which was defined by raising several questions about the nature of the relationship and influence between the independent variable and the dependent variable. For this purpose, a hypothetical scheme was designed that expressed two hypotheses that were subjected to statistical tests to verify their validity. The questionnaire was used as a means of obtaining data. The research adopted the descriptive analytical approach. The research community represented all managers in Korek Telecom Company in the Kurdistan Region of Iraq, and their number reached (150) managers. Due to the small size of the community, the researcher decided to adopt the comprehensive enumeration method to determine the sample, as the forms were distributed to them and only (127) forms were retrieved, thus the response rate reached (84.7%). The hypotheses were tested using the computer program (SPSS V26). The research reached a set of conclusions, including the presence of a significant positive relationship between the dimensions of smart leadership and strategic recovery at the macro and micro levels, in addition to the presence of a positive impact of the smart leadership variable on the strategic recovery variable. The research recommended a set of recommendations, the most important of which is the need to invest in the strong relationship between the two variables and direct this relationship towards serving the Korek company under study.